Psychometrics properties of the Persian version of Beck Anxiety Inventory in North of Iranian adolescents - Khesht Masjedi, Mahnaz Fallahi; Omar, Zoharah; Kafi Masoleh, Seyed Mousa (Medknow Publications, 2015)
Aim: This study investigated the psychometric properties of the Persian Version of the Beck Anxiety Inventory (BAI) for adolescents. Materials and Methods: This research examined the validity and reliability of BAI in North of Iranian normal population. After psychologists had been sufficiently prepared, they were dispatched to different regions of the Guilan (Guilan Province of Iran), referring to residential places for boys and girls in the research. At the end, 783 respondents were randomly recruited and tested using BAI. Two hundred and thirty-two respondents were randomly selected and re-tested in order to measure test-retest reliability with a 1-week interval time between first and second tests. To assess validity; we performed a principal component exploratory factor analysis to explore the factor structure of the BAI and Pearson's correlation coefficient performed for convergent validity between the BAI, self-rating anxiety scale, symptom check list-90-R, sexual abuse trauma index and divergent validity with Beck Depression Inventory (BDI)-II. For data reduction and analysis, the SPSS 22 and Amos 18 were conducted. Result: Findings showed that the Persian version of BAI proved an acceptable test-retest reliability (r = 0.67), an internal consistency (α =0.88), convergent validity (0.40-0.44), and divergent validity (r = 0.216) with BDI-II. We found a clear cut point for our society and these findings confirmed the confirmatory factor analysis results and suggested that the factor structure for the BAI-Iranian is valid and stable. The indices were the Chi-square statistics (χ2 df =547.234), the comparative fit index =0.91), the standardized root-mean-square (0.05), the root-mean-square error of approximation (0.04), and the Akaike Information Criteria (694) a good model fit is indicated. Conclusion: The results support the applicability of BAI in adolescents and suggest the use of this inventory for screening general anxiety by school counselors and psychologists adolescents and research aims.